BRIEF REPORT: Internal Medicine Residents', Attendings', and Nurses' Perceptions of the Night Float System - Akl, Elie A (Blackwell Science Inc, 2006)
BACKGROUND: Residency training programs use the night float system increasingly to meet the new resident work hour regulations. OBJECTIVE: To assess and compare residents', attendings', and nurses' perceptions of the night float system. DESIGN: A survey study. PARTICIPANTS: One hundred and seven residents, 48 attendings, and 69 nurses in a university-based multicenter internal medicine residency program. MEASUREMENTS: Perceived impact on patient care, resident training, and resident performance. RESULTS: The overall response rate was 75%. In general, more residents than both attendings and nurses had positive opinions regarding the night float system, particularly in relation to patient care. Only a small proportion of residents and attendings thought positively about the night float's impact on training quality (29.9%; 18.2%), daily feedback (23.0%; 9.1%), and end of rotation evaluation (21.8%; 6.1%). Less than half of the nurses had positive perceptions of the night residents' performance in terms of promptness (40.9%), physical availability (38.6%), familiarity with the patients' cases, and management plans (15.9%), communication of management plans to nurses (36.4%), professional respect and trust (43.2%), and teamwork (45.5%). CONCLUSIONS: Residents had more positive perceptions than attendings and nurses. Nurses, in particular, had negative perceptions of resident performance in the setting of the night float system.